Attitudes of the public in Maysan city regarding the work of health personnel in light of the Kurna pandemic - Leith Sabbar Jaber ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The research deals with revealing the trends forming among the public of Maysan city regarding the work of health cadres in light of the Corona pandemic, and the medical and humanitarian services provided by these cadres that saved the lives of many, whether by direct contact with members of society, treating the injured or promoting health awareness, so these trends have undergone major changes in Recently after the Corona pandemic, positive impressions were formed in the minds of the public as a result of the moral support provided by the health cadres and various services in the field of prevention, fumigation and health treatment protocols, given that trends are formed through the process of interaction that occurs in different social situations and is acquired by the individual through upbringing. The social family, school, or group to which he belongs as well as the influence of the media.